Impactos do temperamento das matrizes bovinas durante a gestação sob as respostas comportamentais do par vaca-bezerro - Cocco, Joziane Michelon (2024)
This research aims to investigate the effect of the temperament of pregnant bovine dams during gestation and the behavioral effects they impart on the cow-calf relationship. To this end, seventy-six pregnant dams, raised in an extensive system and resulting from rotational crossbreeding between Charolais and Nelore breeds, were divided into two groups based on temperament score assessed during gestation: Adequate (composite scale score ≤ 3) or Reactive (composite scale score > 3). During gestation, dams with reactive temperament demonstrated higher scale scores (average of 4.07 points) and shorter exit time (average of 1.95 points) compared to those with adequate temperament. Calves from dams classified as having adequate or reactive temperament did not show significant differences in the variables of scale score (EB), exit time (TS), and exit speed (VS). However, when analyzing days 75 and 205 of age, it was observed that the calves at 75 days took longer to complete the established route, while the same calves at 205 days demonstrated a higher exit speed. In the evaluation of maternal protection score, most of the mothers were classified as calm and attentive, regardless of temperament. Reactive cows took longer to touch the calf compared to those with adequate temperament, with an average of 40.59s versus 20.62s. Evaluating early weaning and its effects during the first three days of separation, it was observed that behavioral variables were not influenced by maternal temperament; however, the day of evaluation showed a significant influence. Calf vocalization during weaning was more intense initially, decreasing over the days. Calf standing time remained generally stable over the three days of evaluation, averaging 7 hours for offspring of mothers in the adequate treatment group but was higher for those of reactive mothers on the first day compared to the second, averaging 8 hours versus 5 hours and 60 minutes, respectively. Furthermore, the introduction of environmental enrichment promoted positive interaction with objects, varying between groups on different days, with calves from mothers with adequate temperament interacting more with objects on the first day (47 minutes), while on the second day, this behavior was observed in calves of reactive mothers (47 minutes). The behavior of the mothers during early weaning was evaluated over two days, their temperament did not directly influence it, however, considering the evaluation day, there was greater vigilance from the mothers on the first day, which decreased over time. Finally, the results obtained suggest that reactive cows take longer to reestablish contact with their calves after a brief separation. Additionally, this research evidenced that the temperament of the dam during gestation did not affect the respective calf, and the changes observed in them may be a reflection of the environment.